2017
DOI: 10.1210/jc.2016-3837
|View full text |Cite
|
Sign up to set email alerts
|

Early Prenatal Phthalate Exposure, Sex Steroid Hormones, and Birth Outcomes

Abstract: Context: Adequate sex steroid hormone concentrations are essential for normal fetal genital development in early pregnancy. Our previous study demonstrated an inverse relationship between third-trimester di-2-ethyl hexyl phthalate exposure and total testosterone (TT) concentrations. Here, we examine earlypregnancy phthalates, sex steroid hormone concentrations, and newborn reproductive outcomes. Design:We examined associations between urinary phthalate metabolite concentrations in early pregnancy and serum fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
81
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 54 publications
5
81
0
Order By: Relevance
“…18 Prenatal phthalate exposure has been associated with a shorter male anogenital distance [19][20][21] and male genital defects. 22 Such changes to the male genitals may arise from phthalate-induced suppression of fetal gonadal testosterone synthesis. 23 Antiandrogenic phthalates have been shown to disrupt testosterone-dependent brain development, 24 and associations between prenatal exposure and sex-dependent neurodevelopmental end points have been reported.…”
mentioning
confidence: 99%
“…18 Prenatal phthalate exposure has been associated with a shorter male anogenital distance [19][20][21] and male genital defects. 22 Such changes to the male genitals may arise from phthalate-induced suppression of fetal gonadal testosterone synthesis. 23 Antiandrogenic phthalates have been shown to disrupt testosterone-dependent brain development, 24 and associations between prenatal exposure and sex-dependent neurodevelopmental end points have been reported.…”
mentioning
confidence: 99%
“…Bottlenose dolphin exposure to DEHP and DEP is concerning due to laboratory and human studies linking these chemicals to adverse health effects including altered hormone synthesis and transport (ATSDR, ; Meeker & Ferguson, ; Sathyanarayana et al, ], male genital developmental abnormalities (ATSDR, ; Swan, ), reproductive impairment (e.g., lower birth weight, Messerlian et al, ; preterm birth, Meeker et al, ; delayed time to pregnancy, Thomsen et al, ; pregnancy loss, H. Gao et al, ), and liver toxicoses including liver cancer (ATSDR, ). In fact, MEHP concentrations measured in the dolphins in this study (GM = 1.9 ng/ml; Range = 0.9–5.9 ng/ml) were at comparable levels reported to be associated with a reduced probability of reproductive success in humans (Hauser et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Certain phthalates have been identified as reproductive and developmental toxicants and endocrine disruptors. Mammalian toxicological studies have suggested that some phthalate compounds can disrupt the secretion of thyroid and growth hormones (Mathieu-Denoncourt et al, 2015), alter steroidogenesis and lower circulating concentrations of testosterone (Bell, 1982;Meeker & Ferguson, 2014;Sathyanarayana et al, 2017), and impact the production and metabolism of estrogen (Sathyanarayana et al, 2017). The consequences of these hormonal changes may result in reduced fertility, abnormal reproductive organ development, and impacts on pregnancy outcomes (Bell, 1982;Latini et al, 2004).…”
Section: Introduction To Phthalates and Potential Health Concernsmentioning
confidence: 99%
“…Previous studies have shown associations between markers of phthalate and BPA exposure and altered steroid hormone levels in adults (Ehrlich et al 2012; Meeker et al 2009; Mok-Lin et al 2010; Pan et al 2006; Sathyanarayana et al 2014; Sathyanarayana et al 2017), as well as associations between in utero or early life exposure and hormone levels in infants (Araki et al 2014; Lin et al 2011; Main et al 2006). However, few studies have investigated relationships between phthalate or BPA exposure during in utero development and subsequent hormone levels during puberty, a time at which steroid hormones play an essential role in reproductive development.…”
Section: Introductionmentioning
confidence: 99%